Development of a pattern-based numeracy learning module to enhance students' creative thinking and numeracy skills - Yesi Yuniati; Tatag Yuli Eko Siswono; Tri Dyah Prastiti (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Numeracy and creative thinking are essential skills for elementary students to solve contextual and complex mathematical problems. This study aims to develop and evaluate a numeracy learning module based on number and visual patterns for fourth-grade students. A research and development approach was applied using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The module was validated by content and media experts, and tested at SDN Banjarkemuning and SDN Semampir 1. Data were collected through expert validation sheets, implementation observations, student response questionnaires, and pretest–posttest instruments. The validation process indicated that the module met high standards of content quality, clarity of language, presentation, and visual design. The implementation of the module resulted in a significant improvement in students' numeracy and creative thinking skills, as reflected in the posttest score gains. The study's main contribution lies in integrating numeracy and creativity in a single contextual, activity-based teaching tool. These findings support the potential of structured and contextualized numeracy instruction to enhance conceptual understanding and student engagement. The implications suggest that such modules can be effectively adopted to enrich elementary mathematics instruction and curriculum design.